2006
DOI: 10.1186/1479-7364-2-4-212
|View full text |Cite
|
Sign up to set email alerts
|

Inference of ancestry: constructing hierarchical reference populations and assigning unknown individuals

Abstract: The ability to infer personal genetic ancestry is being increasingly utilised in certain medical and forensic situations. Herein, the unsupervised Bayesian clustering algorithms structure, is employed to analyse 377 autosomal short tandem repeats typed on 1,056 individuals from the Centre d'Etude du Polymorphisme Humain Human Diversity Panel. Individuals of known geographical origin were hierarchically classified into a framework of increasingly homogeneous clusters to serve as reference populations into which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Similar effects in densely sampled areas have been reported in other studies (e.g. Ekins et al 2006) and may be seen as an effect of isolation by distance. We addressed this problem by introducing intermediate populations (0.4 < Q < 0.6) e.g.…”
Section: Final Results and Discussionsupporting
confidence: 88%
“…Similar effects in densely sampled areas have been reported in other studies (e.g. Ekins et al 2006) and may be seen as an effect of isolation by distance. We addressed this problem by introducing intermediate populations (0.4 < Q < 0.6) e.g.…”
Section: Final Results and Discussionsupporting
confidence: 88%
“…comm.). The hierarchical population structure analysis of Ekins et al (2006) further suggested the presence in the diversity panel of many additional groups of related individuals.…”
Section: Relative Pairsmentioning
confidence: 96%
“…Inference of the ethnic origin of a suspect from their DNA recovered from a crime scene sample can act as 'investigative intelligence' and help enforcement agencies concentrate their resources in the absence of any other suspect specific information. This idea is not new and has been explored extensively in the literature through the development and application of assignment approaches that use genetic markers to identify unique genetic groups or populations [1][2][3]. The specific identification of Ancestry Informative Markers (AIMs) panels that are particularly powerful at inferring ethnic origin has also been the focus of much research and the assessment of different classes of molecular marker has slowly moved from mitochondrial DNA (mtDNA) sequence variation, through autosomal and Y linked Short Tandem Repeat (STRs) markers to Single Nucleotide Polymorphisms (SNPs) [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%